DNA Profile of White Male Rats Spermatozoa after Treatment with Tannins Beluntas (Pluchea indica) - Susetyarini, Eko; Latifa, Roimil; Jaya Miharja, Fuad (International Journal of Engineering and Technology, 2019)
Traditional plants developed and used as anti-fertility are still considerably rare in the modern days. One of the recognized anti-fertility plants vailable in the tropical country of Indonesia is is the leaves of Beluntas plant. In general, Beluntas dried leaves contain 1.885% tannin. Past research on beluntas tannin that has been carried out, the fraction of tannins can reduce the potential fertilization of rat spermatozoa, decreasing the number of spermatogenic cells, has no effect on the amino acid composition of semens. However, these studies did not evaluate the role of the tannin fraction in mitochondrial DNA profile spermatozoa. The aim of research to study the leaf tannins giving beluntas in mtDNA genetic profile of rats spermatozoa. This type of research is experimental approach. The research sample include 12 male rats weights about 250-300 mg, at the age 3 months old. The design research is also conducted on: the control rat group, without being treated. Group II is divided into five treatment, the group was given beluntas leaf tannin. Giving beluntas leaf tannins administered orally as 0.8 ml (an effective dose of tannins in inhibiting fertilization of previous studies) to the rats every other day for 98 days. Observations when giving treatment with an interval of 49 + 3 days, 49-day + 16, 49 + 26-day, 49-day + 36, 49 + 49 days (previous studies) on spermatozoa mtDNA profile. Spermatozoa were taken from the epididymis organ. Analysis of mtDNA genetic profiles using PCR. Analysis of the data used quantitative descriptive. The results showed that the spermatozoa DNA molecular weight in the range of 599-611 bp. Beluntas tannin giving treatment showed no effect on the molecular weight of DNA base pairs spermatozoa male rats.Â Â